Application of A Judge's Ruled In A Civil Dispute - Fransiskus Kandunmas; Rieta Lieke Lontoh; Primus Aryesam (Faculty of Law, Universitas Pattimura, 2022)
In 2005, the trial of land grant dispute was held between the Diocese of Amboina as the plaintiff against MR et al. as a defendant in the District Court Tual Southeast Moluccas. This trial was won by the Diocese of Amboina. The defendant then filed an appeal, Cassation and judicial review up to the level of the Supreme Court. Based on the Supreme Court decision no. 166/Pk / year 2010, the panel of judges ruled that the Diocese of Amboina as the legal owner of the land and sentenced the defendant to pay a fine and return the object of dispute without any conditions. Since the issuance of the decision until now, the Diocese of Amboina has not executed the land object, because the Diocese of Amboina has not submitted an application for execution to the District Court in accordance with the provisions of Article 196 HIR due to normative juridical considerations of the church; humanitarian reasons and the urgency of utilizing the object of dispute.. The purpose of this research is to understand the application of Supreme Court decision No. 166/Pk/Pdt / 2010 in dispute over land grant Diocese of Amboina. The author uses normative juridical methods and also through interviews to obtain information as a support in writing this thesis. The result of the research found that decision has permanent force and for the realization of justice and legal certainty for the parties, especially the Diocese of Amboina, the execution action must be carried out immediately in cooperation with the local district court.